To find the recursive formula for the given arithmetic sequence: 7, 5, 3, 1, −1, ..., we need to identify the first term and the common difference.
- The first term \( a_1 \) is 7.
- The common difference \( d \) can be calculated as:
- \( 5 - 7 = -2 \)
- \( 3 - 5 = -2 \)
- \( 1 - 3 = -2 \)
- \( -1 - 1 = -2 \)
The common difference is \( -2 \).
Now we can express the recursive formula:
- The first term is \( a_1 = 7 \).
- The general recursive relation can be stated as: \[ a_n = a_{n-1} - 2 \] for \( n > 1 \).
Combining these, the recursive formula is:
- \( a_1 = 7 \)
- \( a_n = a_{n-1} - 2 \)
The correct response is: a1=7, an=an−1−2